2023
DOI: 10.3897/neobiota.84.89826
|View full text |Cite
|
Sign up to set email alerts
|

Cosmopolitan Scolytinae: strong common drivers, but too many singularities for accurate prediction

Abstract: Many scolytine beetle species have been expanding in new territories, travelling with wood and plants for planting, sometimes with a high impact on plant health. Here, we attempt to quantify the mobility of these species and to identify the biological drivers of mobility and impact. Mobility was estimated by counting the numbers of landmasses (contiguous pieces of land, surrounded by ocean or sea) colonised by each species. A series of potential drivers (taxonomic tribes; feeding regimes; polyphagy; reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Research has repeatedly highlighted that inbreeding is a characteristic seen in many exotic Scolytinae species (Jordal et al 2001;Grousset et al 2020;Lantschner et al 2020;Demidko et al 2021;Grégoire et al 2023). A review looking at 163 scolytines with invasion histories (SIHs: Scolytinae species with an invasion history) found that 53% engage regularly in inbreeding, compared to the 27% seen among all Scolytinae (Grégoire et al 2023). Some of these inbreeding species display mixed breeding-the possibility of mating with neighboring, non-related individuals when population densities are high.…”
Section: The Consequences Of Preemergence Mating and Inbreeding For I...mentioning
confidence: 99%
“…Research has repeatedly highlighted that inbreeding is a characteristic seen in many exotic Scolytinae species (Jordal et al 2001;Grousset et al 2020;Lantschner et al 2020;Demidko et al 2021;Grégoire et al 2023). A review looking at 163 scolytines with invasion histories (SIHs: Scolytinae species with an invasion history) found that 53% engage regularly in inbreeding, compared to the 27% seen among all Scolytinae (Grégoire et al 2023). Some of these inbreeding species display mixed breeding-the possibility of mating with neighboring, non-related individuals when population densities are high.…”
Section: The Consequences Of Preemergence Mating and Inbreeding For I...mentioning
confidence: 99%
“…Several species within this group are widely acknowledged as significant agents of tree mortality in coniferous forests globally (Raffa et al 2008; Biedermann et al 2019). Additionally, they are inadvertently transported via wood products and wood packaging materials, and numerous species have effectively established worldwide, constituting a notable group of invasive forest insects (Lantschner et al 2020; Grégoire et al 2023).…”
Section: Introductionmentioning
confidence: 99%